IADC/SPE Asia Pacific Drilling Technology Conference and Exhibition 2012
DOI: 10.2118/155799-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Adjustable Frequency Pulse Jet Generating Tool to Improve Rate of Penetration in Deep Wells

Abstract: Improving the rate of penetration in deep well is long-term problems for drilling industry. Pulsed jet drilling which has been proved in field, is a cost-effective way to improve the rate of penetration. An Adjustable frequency pulsed jet generating tool was developed in this paper. The main parts of the adjustable frequency pulsed jet generating tool include turbine, valves, and a resonance pulse chamber. Rotary valve is driven by the turbine. Rotation of the rotary valve causes the state of drilling fluid fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Previous research on pulse drilling fluid has mainly centered on improving rock breaking efficiency and ROP [33,34]. There has been little analysis to date on the impact of pulse drilling fluid on cuttings transport.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on pulse drilling fluid has mainly centered on improving rock breaking efficiency and ROP [33,34]. There has been little analysis to date on the impact of pulse drilling fluid on cuttings transport.…”
Section: Introductionmentioning
confidence: 99%
“…This provides a continuous impact on the cuttings by changing the flow rate of the drilling fluid. Pulsed jet drilling technology can effectively increase the drilling speed [27], and so downhole drilling tools using pulsed jets are equipped with variable-frequency pulse jet generators [28] and spiral pressure intensifiers [29]. Field experiments have shown that the use of pulsed drilling fluid reduces the effect of chipping and increases the efficiency of cuttings transport [30,31].To date, the focuses of most studies of cuttings transport have been on its behavior of cuttings under conventional drilling fluid flow conditions.…”
mentioning
confidence: 99%
“…1,2 Therefore, it is urgent to seek available cost-effective rockbreaking methods for improving the penetration rate in hard formations of deep wells. 1,2 Therefore, it is urgent to seek available cost-effective rockbreaking methods for improving the penetration rate in hard formations of deep wells.…”
mentioning
confidence: 99%
“…hardness, and abrasiveness of the rock increase as the well depth increases, resulting in poorer drilling ability, lower penetration rate, longer drilling cycles, and higher cost. 1,2 Therefore, it is urgent to seek available cost-effective rockbreaking methods for improving the penetration rate in hard formations of deep wells. 3,4 A high-pressure waterjet is considered one of the most promising assisted rock-breaking technologies.…”
mentioning
confidence: 99%